Pediatric Anti-N-methyl-D-aspartate Receptor Encephalitis Mimicking Glutaric Aciduria Type 1: A Case Report - Valle, Daniel Almeida do; Santos, Mara Lúcia Schmitz Ferreira; Zeny, Michelle Silva; Cordeiro, Mara L. (Frontiers in Neurology, 2020)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is an immune-mediated disease that induces a wide spectrum of symptoms, especially in toddlers. These include acute-onset movement disorders, with neurological regression, and other associated neurological symptoms. Anti-NMDAR encephalitis remains a diagnostic challenge, especially in toddlers, with better prognosis associated with early treatment. We report the case of a 15-month-old boy who initially presented with vomiting and later with acute-onset dystonia after the administration of antiemetics. Within 14 days, the patient developed neuropsychomotor developmental regression and worsening dystonia. After ruling out an acute dystonic reaction and glutaric acidemia type 1 (GA-1), a final diagnosis of anti-NMDAR encephalitis was made. The patient responded well to immunomodulatory therapy. The present case underscores the importance of early treatment for patient prognosis and of including anti-NMDAR encephalitis in the differential diagnosis of acute-onset movement disorders.